Ediacaran marine animal forests and the ventilation of the oceans - Gutarra, S; Mitchell, EG; Dunn, F; Gibson, BM; Racicot, RA; Darroch, SAF; Rahman, I (Cell Press, 2024)
The rise of animals across the Ediacaran–Cambrian transition marked a step-change in the history of life, from a microbially-dominated world to the complex macroscopic biosphere we see today. While the importance of bioturbation and swimming in altering the structure and function of Earth systems is well established, the influence of epifaunal animals on the hydrodynamics of marine environments is not well understood. Of particular interest are the oldest ‘marine animal forests’, which comprise a diversity of sessile soft-bodied organisms dominated by the fractally-branching rangeomorphs. Typified by fossil assemblages from the Ediacaran of Mistaken Point, Newfoundland, these ancient communities might have played a pivotal role in structuring marine environments, similar to modern ecosystems, but our understanding of how they impacted fluid flow in the water column is limited. Here, we use ecological modelling and computational flow simulations to explore how Ediacaran marine animal forests influenced their surrounding environment. Our results reveal how organism morphology and community structure and composition combined to impact vertical mixing of the surrounding water. We find that Mistaken Point communities were capable of generating high-mixing conditions, thereby likely promoting gas and nutrient transport within the ‘canopy’. This mixing could have served to enhance local-scale oxygen concentrations and redistribute resources like dissolved organic carbon. Our work suggests that Ediacaran marine animal forests may have contributed to the ventilation of the oceans over 560 million years ago, well before the Cambrian explosion of animals.